PENGGUNAAN METODE TUTOR SEBAYA SELAMA PEMBELAJARAN DARING UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA - Karo, Karmila Br (Jurnal Ilmiah Aquinas, 2022)
This type of research is classroom action research. The purpose of this study was to find out how the results of the implementation of learning with the Application of Peer Tutor Online Learning Methods to Improve Learning Activeness of Class XI Science Students at SMA Negeri 1 Kutabuluh in the 2021/2022 Academic Year. Based on the results of research and discussion, classroom action research carried out on class XI students of SMA Negeri 1 Kutabuluh, it can be concluded as follows: (1) The application of Peer Tutor learning methods can increase student learning activity, seen from the acquisition of the average percentage of student learning activeness in the first cycle of 46.3%, then increased at the second cycle meeting of 67.1%. (2) The application of Peer Tutor learning methods can improve student learning outcomes in cognitive and psychomotor aspects. The percentage of completeness of students' cognitive learning outcomes before the application of the Peer Tutor learning method was 51.61%, then it increased in the first cycle by 9.69% to 61.3%. An increase also occurred from cycle I to cycle II by 16.1% to 77.4%. The percentage of students' completeness in the psychomotor aspect in the pre-cycle is 64.51%. An increase in the completeness of the assessment on the psychomotor aspect occurred in the pre-cycle to the first cycle by 12.89% to 77.4%, the percentage of completeness of the performance assessment results increased again from the first cycle to the second cycle by 9.6% to 87%.